PENTINGNYA INTERAKSI GURU DAN SISWA DALAM PEMBELAJARAN JARAK JAUH - Evi Rizqi Salamah (PROCEEDING UMSURABAYA, 2022)
This study aims to describe how important the interaction of teachers and students in distance learning is. The research method used is qualitative research, with data collection techniques in the form of observation and interviews. The focus of this research is to examine recent research on the importance of interaction in learning compared to other things and to briefly describe the types of interactions that have been used in distance education, explain the importance of designing interactions into distance learning environments, and design steps for learning steps that can facilitate interaction effectively. The results of this study indicate that the quality of interaction in distance learning still needs to be improved by focusing on teacher and student interactions.Â Keywords: Distance education; Type of interaction, Teacher and student interaction; Interaction design